IN VITRO ANTI-ACETYL CHOLINESTERASE AND ANTIOXIDANT ACTIVITY OF SELECTED MALAYSIAN PLANTS - H. Nour, Azhari; Khan, Muhammad; Sulaiman, Ahmad Ziad; Batool, Tahira; H. Nour, ABDURAHMAN; Mumtaz Khan, Muhammad; Kormin, Faridah (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of this study is to discover and identify the potential plant extracts that could be vital against Alzheimer's disease (AD). It is a neurodegenerative disease affecting the brain. The most promising target for the symptomatic treatment and slowing of AD progression is cholinesterase inhibitors from plants. Methods: To evaluate the antioxidant and anti-acetylcholinesterase (AChEI) activities leaves and roots were macerated and refluxed with ethanol extracts, from four medicinal plants, namely; C.asiatica, M.pudica, C.pumila, and L.camara. DPPH and β-carotene assays were used to determine antioxidant activity; whereas Ellman's colorimetric method was adopted to quantify AChEI activity. Results: The refluxed ethanol extract of M.pudica leaves exhibited the highest AChEI activity (IC50 = 0.047 mg/ml) and high antioxidant activity (β-carotene; IC50 = 0.14 mg/ml and DPPH; IC50 = 0.012 mg/ml). Conclusion: Results reveal that all plant extracts studied possess anti-oxidant properties. Most potent extracts could be a lead to novel antioxidants and acetyl cholinesterase inhibitors, for the treatment of AD. Keywords; Alzheimer's disease (AD); Acetylcholinesterase activity; Antioxidant activity; β-carotene; DPPH; Medicinal plants.